1976
DOI: 10.1007/bf02908691
|View full text |Cite
|
Sign up to set email alerts
|

The influence of cations and methylamine on structure and function of thylakoid membranes from barley chloroplasts

Abstract: The effects of cations on the structure and activity of isolated barley (Hordeum vulgare cv. Sval6fs Bonus) chloroplast lamellar systems were studied. Three separate effects of cations were recognizable. (I) Cations in high concentrations (in excess of 100-200 mM NaCI) are required to maintain granal stacks once the outer chloroplast envelope is broken. In 30 mM NaCI the majority of the lamellar systems exist as well-separated thylakoids, even in the presence of high concentrations of sucrose (330 and 660 mM).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

1979
1979
2001
2001

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…Results of studies we reported earlier showed that wild type barley chloroplasts prepared as described in this report consist of naked lamellar systems with almost no grana (18). Salt concentrations higher than those used in the isolation media, or those used in the assay mixtures, would be required if grana structure were to have been maintained, or if appression between adjacent thylakoids were to have been re-established (18 Despite the lack of grana, the chloroplast preparations catalyzed high rates of electron transport from water to both ferricyanide and DCIP, and were able to establish proton concentration gradients across membranes in the light.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Results of studies we reported earlier showed that wild type barley chloroplasts prepared as described in this report consist of naked lamellar systems with almost no grana (18). Salt concentrations higher than those used in the isolation media, or those used in the assay mixtures, would be required if grana structure were to have been maintained, or if appression between adjacent thylakoids were to have been re-established (18 Despite the lack of grana, the chloroplast preparations catalyzed high rates of electron transport from water to both ferricyanide and DCIP, and were able to establish proton concentration gradients across membranes in the light.…”
Section: Discussionsupporting
confidence: 53%
“…Salt concentrations higher than those used in the isolation media, or those used in the assay mixtures, would be required if grana structure were to have been maintained, or if appression between adjacent thylakoids were to have been re-established (18 Despite the lack of grana, the chloroplast preparations catalyzed high rates of electron transport from water to both ferricyanide and DCIP, and were able to establish proton concentration gradients across membranes in the light. These activities had the expected sensitivities to various uncouplers, phenylenediamine, DCMU, and dibromothymoquinone (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chloroplasts were isolated as described previously (24) and photochemical activities assayed at 23°C using an Aminco DW-2 spectrophotometer (American Instrument Co.) with saturating red-light side illumination. The assay mixture (1.5 ml) contained chloroplasts (4 ,ug Chl ml-'), 50 'Abbreviations: PD, p-phenylenediamine; DBMIB, 2,5-dibromo-3-methyl-6-isopropyl-p-benzoquinone.…”
Section: Materials and Methods Sugar Beet (Beta Vulgaris L) Sunflowmentioning
confidence: 99%
“…The thylakoid membranes carry a net negative charge, but the presence of cations, especially divalent cations, keeps the thylakoid membranes stacked by screening the electrostatic repulsion (Barber, 1980(Barber, , 1982Sculley et al, 1980). NaCl was included at 10 mm to avoid osmotic swelling and rupture of the thylakoid membranes, but this concentration is still sufficiently low to allow destacking (Smillie et al, 1976). To facilitate migration and randomization of the photosynthetic complexes in the destacked thylakoid membranes (Sundby et al, 1986), the membranes were further incubated for 40 min at 20°C at approximately 2 mg of chlorophyll per milliliter after the last resuspension in 10 mm Bis-Tris (pH 6.8), 100 mm Suc, and 10 mm NaCl.…”
Section: Isolation Of Thylakoid Membranesmentioning
confidence: 99%